2021
DOI: 10.1177/17562848211042200
|View full text |Cite
|
Sign up to set email alerts
|

Primary care and referring physician perspectives on non-alcoholic fatty liver disease management: a nationwide survey

Abstract: Introduction: The optimal approach to screening and risk stratification for non-alcoholic fatty liver disease is challenging given disease burden and variable progression. The aim of this study was to assess primary care physician and referring physician practice patterns regarding non-alcoholic fatty liver disease. Methods: An anonymous nationwide survey was administered to primary care physicians, endocrinologists, and cardiologists in a: (1) tertiary academic hospital, (2) community hospital, and (3) the Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…One third of the respondents referred all or most of their patients with NAFLD to a specialist, whereas up to 10% referred none. This was in part due to lack of clinical tools for risk stratification, as less than 5% of community physicians reported using noninvasive diagnostic markers 9…”
Section: Introductionmentioning
confidence: 99%
“…One third of the respondents referred all or most of their patients with NAFLD to a specialist, whereas up to 10% referred none. This was in part due to lack of clinical tools for risk stratification, as less than 5% of community physicians reported using noninvasive diagnostic markers 9…”
Section: Introductionmentioning
confidence: 99%
“…Reasons cited for this lack of referral included cost concerns and lack of patient interest, primarily. 12 Altogether, these data suggest a substantial need to improve coordination of care among referring clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons cited for this lack of referral included cost concerns and lack of patient interest, primarily. 12 Altogether, these data suggest a substantial need to improve coordination of care among referring clinicians. While hepatologists and gastroenterologists appear relatively likely to use the AASLD guidelines to help inform their patient management, 24% of PCPs and 33% of endocrinologists reported not using any guidelines for NAFLD/NASH management.…”
mentioning
confidence: 99%
“…These phenomena result in a substantial disconnect between current guidelines and real-world clinical practice. 30,31 Alarmingly, a recent study demonstrated that 71% of primary care patients had a non-invasive fibrosis score (Fibrosis-4 Index and NAFLD Fibrosis Score) in the indeterminate-risk or high-risk category for advanced fibrosis, reinforcing the clinical significance of knowledge deficits regarding diagnosis, although being the major determinant of complications. 29 Primary care uptake might be hampered by the limited involvement of primary care physicians in the development of clinical practice guidelines.…”
Section: Iag Nos Is and Screening Barrier Smentioning
confidence: 99%
“…Reasons for these diagnostic errors are complex, with survey studies showing that NAFLD is not perceived as a priority in primary care, and there is a large knowledge deficit regarding NAFLD diagnosis and management. These phenomena result in a substantial disconnect between current guidelines and real‐world clinical practice 30,31 . Alarmingly, a recent study demonstrated that 71% of primary care patients had a non‐invasive fibrosis score (Fibrosis‐4 Index [FIB‐4] and NAFLD Fibrosis Score) in the indeterminate‐risk or high‐risk category for advanced fibrosis, reinforcing the clinical significance of knowledge deficits regarding diagnosis, although being the major determinant of complications 29 .…”
Section: Diagnosis and Screening Barriersmentioning
confidence: 99%